Characterization of diffusionnal transfers of bound water and water vapor in beech and spruce - Mouchot, N.; Thiercelin, F.; Perre, P.; Zoulalian, A. (Maderas. Ciencia y Tecnología, 2025)
In the hygroscopic range of wood and without any thermal gradient, transfer of water vapor and bound water is carried out by diffusion. In this study, we experimentally determined the diffusivity values for vapor and bound water in the three orthotropic directions of wood for two species (beech and spruce). We then evaluated in steady-state the fluxes for the two forms of water and showed the influence of wood morphologies and transfer direction on these fluxes.